A framework for periodized nutrition for athletics - Stellingwerff, T.; Morton, J. P.; Burke, L. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
The concept and underpinnings of periodization are deeply rooted in the history of athletics (track and field). Indeed, the seminal scientists and coaches who developed the principles of periodization include Dr. Hans Selye with his General Adaptation Syndrome model (Selye, 1950), followed by Matveyev, Bonderchuck, and Bompa (contributions reviewed by Issurin, 2010). Numerous approaches to periodization have emerged from this work, including classical, block, polarized, and complex models (Issurin, 2010; Kiely, 2012). Within this diversity is a central theme: the purposeful sequencing of different training units (long [macrocycle; months], medium [mesocycle; weeks], and short [microcycle; days and within-day duration]) so that athletes can attain the desired readiness to perform optimally for targeted events on demand (Stone et al., 1981). However, it is now appreciated that the chaos and complexities of the individual, exposed to various stimuli (physical, emotional, and genetic), are probably much more complicated than most periodization purists would want to admit (Kiely, 2018). Furthermore, the impact of nutrition on training adaptation and performance needs to be recognized.